2001
DOI: 10.3354/meps212145
|View full text |Cite
|
Sign up to set email alerts
|

The role of digestive surfactants in determining bioavailability of sediment-bound hydrophobic organic contaminants to 2 deposit-feeding polychaetes

Abstract: Solubilization of sediment-bound hydrophobic contaminants (HOCs) by gut fluids of deposit-feeding polychaetes greatly exceeds solubilization by seawater. We present evidence that digestive surfactants exert a central role in HOC desorption, and that the degree of in vitro solubilization by gut fluids is an excellent predictor of HOC absorption efficiency (AE) by the respective worm species. We compared in vitro solubilization of sediment-bound 14 C-hexachlorobenzene (HCB) and 14 C-tetrachlorobiphenyl (TCBP) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 33 publications
7
79
0
Order By: Relevance
“…The lower AE values noted for killifish compared to deposit-feeding polychaetes and bivalves could be a result of the difference in gut physiology among these organisms. The pH of gut fluid in worms (pH 6.88 in Nereis succinea; Ahrens et al 2001) and bivalves (pH 5.0 in the clam Macoma balthica and 5.6 in the mussel Mytilus edulis; Griscom et al 2002b) is neutral or mildly acidic, whereas the pH of killifish gut fluid is mildly acidic to alkaline. A study by Babkin & Bowie (1928) determined that the intestinal fluid in fasting killifish has a pH between 8.0 and 9.2, and fish have a pH between 8.4 and 9.0 after feeding on clams.…”
Section: Assimilation Of Metals After Sediment Intubationmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower AE values noted for killifish compared to deposit-feeding polychaetes and bivalves could be a result of the difference in gut physiology among these organisms. The pH of gut fluid in worms (pH 6.88 in Nereis succinea; Ahrens et al 2001) and bivalves (pH 5.0 in the clam Macoma balthica and 5.6 in the mussel Mytilus edulis; Griscom et al 2002b) is neutral or mildly acidic, whereas the pH of killifish gut fluid is mildly acidic to alkaline. A study by Babkin & Bowie (1928) determined that the intestinal fluid in fasting killifish has a pH between 8.0 and 9.2, and fish have a pH between 8.4 and 9.0 after feeding on clams.…”
Section: Assimilation Of Metals After Sediment Intubationmentioning
confidence: 99%
“…Furthermore, the killifish does not have a stomach (Babkin & Bowie 1928); because the stomach secretes gastric acid, the absence of the stomach can provide some explanation for the higher pH of the intestinal fluid. Worms also have a high concentration of amino acids in their digestive fluid, which can solubilize metals from sediment, and surfactants that can solubilize polycyclic aromatic hydrocarbons (Mayer et al 1996, Ahrens et al 2001. Mayer et al (1996) investigated the solubility of metals in the gut fluid of the lugworm Arenicola marina and the sea cucumber Parastichopus californicus; the lugworm solubilized more metal as a result of a much higher dissolved amino acid concentration.…”
Section: Assimilation Of Metals After Sediment Intubationmentioning
confidence: 99%
“…data). Some other detailed work on contaminant extractions has been done with the holothuroid Parastichopus californicus (Mayer et al 1996), the echiuran Urechis caupo (Weston and Mayer 1998a), the polychaetes Nereis succinea and Pectinaria gouldii (Ahrens et al 2001), and a survey of 18 species reported in Mayer, Weston, and Bock (2001).…”
Section: Extraction Protocolmentioning
confidence: 99%
“…For hydrophobic organic compounds that have been spiked into the sediment, the duration of extraction is largely irrelevant as most of the contaminant extraction occurs in the first few minutes (Ahrens et al 2001;Weston, unpub. data).…”
Section: Extraction Protocolmentioning
confidence: 99%
“…As a deposit-feeder, polychaetes ingest sediment and digest organic matter in the sediment, before defecating the altered sediment. Some research has indicated that the digestive fluids of deposit-feeders are more effective than water at solubilizing organic materials associated with sediments (Ahrens et al, 2001). In addition, disturbances caused by polychaetes aid the growth of specific bacterial groups, which break down, use, and enrich specific types of organic matter (Cuny et al, 2007).…”
Section: Sediment and Water Improvementmentioning
confidence: 99%